Surviving as Indians : The Challenge of Self-Government - Boldt, Menno, 1930- (Book collections on Project MUSE., 1993)
This book is about a just future for Indians in Canada. It defines justice in terms of the survival and well-being of Indians as Indians, that is, defined by their traditional principles and philosophies, not by the Indian Act or by their experience of colonialism. Menno Boldt calls for social action, not theory, holding that unless Indians revitalize, adapt, and develop their traditional philosophies and principles for living and surviving in the context of Canadian society, polity, and economy, they will become extinct as Indians; they will survive only as a legal-racial category created by the Indian Act. Moreover, Boldt argues, so long as the mass of Indians continue to live in conditions of degrading dependence, destitution, and powerlessness, Indian government will be a travesty.Surviving as Indians examines the roots in injustice to Indians, and then analyses Canadian Indian policies, Indian leadership, culture, and economy. Boldt stresses five imperatives: moral justice for Indians; Canadian policies that treat Indian rights, interests, aspirations, and needs as equal to those of Canadians; Indian leadership that is committed to eliminating the colonial political and bureaucratic structures on their reserves, and to returning Indian government into the hands of their people; revitalizing Indian cultures, languages, and social systems that are adapted and developed within the framework of traditional philosophies and principles; and economic self-sufficiency and independence to be achieved through employment in the Canadian mainstream.The Indians' future must inevitably be worked out with Canadians. Surviving as Indians intends to open a dialogue between the two groups.